2018
DOI: 10.1177/2059204318792319
|View full text |Cite
|
Sign up to set email alerts
|

Musical creativity and the embodied mind

Abstract: The phenomenon of creativity has received a growing amount of attention from scholars working across a range of disciplines. While this research has produced many important insights, it has also traditionally tended to explore creativity in terms of the reception of products or outcomes, conceiving of it as a cognitive process that is limited to the individual domain of the creative agent. More recently, however, researchers have begun to develop perspectives on creativity that highlight the patterns of adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 162 publications
2
77
0
Order By: Relevance
“…Consider how one can develop a particular fingering solution that is easier when practicing alone but can then be re-explored and modified to account for a particular expressive necessity that only emerges when playing with others, leading to online adaptive regulations, or how a phrasing choice can be revisited to convey a better sense of tension, which may be further developed via open discussion with peers and teachers. "Listening" (to themselves and to others) becomes then an enabling condition for meaningful music making, a tool for sonic discoveries that is negotiated and transformed collectively to serve a variety of creative functions (see also van der Schyff et al, 2018;Gutierrez, 2019). Students and performers need to be attuned to their peers, be aware of the environment in which they perform and learn, and adapt themselves to what such a setting may offer.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Consider how one can develop a particular fingering solution that is easier when practicing alone but can then be re-explored and modified to account for a particular expressive necessity that only emerges when playing with others, leading to online adaptive regulations, or how a phrasing choice can be revisited to convey a better sense of tension, which may be further developed via open discussion with peers and teachers. "Listening" (to themselves and to others) becomes then an enabling condition for meaningful music making, a tool for sonic discoveries that is negotiated and transformed collectively to serve a variety of creative functions (see also van der Schyff et al, 2018;Gutierrez, 2019). Students and performers need to be attuned to their peers, be aware of the environment in which they perform and learn, and adapt themselves to what such a setting may offer.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Music-making, in particular, consists of culturally mediated forms of skillful coadaptations which involve a negotiation between the maintenance of an individual "perspective" or "point of view", and the capacity to explore and develop novel experiences and strategies, depending on the context of the performance van der Schyff et al 2018). Even when a particular piece or pattern is repeated over and over, we generally consider it to be an "exploration" over and above a "repetition".…”
Section: Sense-makingmentioning
confidence: 99%
“…In line with such concerns, other scholars (Cross, 1999 , 2001 , 2003 ; Killin, 2013 , 2016a ; van der Schyff, 2013a , b ; Currie and Killin, 2016 ) have offered alternative “biocultural” approaches to the nature and origins of human musicality—where the question of whether either biology or culture should account for deeply social and universal human activities that require complex cognitive functions (e.g., music) is replaced by a perspective that integrates the two. For example, Cross ( 1999 ) suggests that musicality is an emergent activity—or “cognitive capacity”—that arises from a more fundamental human proclivity to search for relevance and meaning in our interactions with the world.…”
Section: The Biocultural Hypothesismentioning
confidence: 88%
“…These last claims are questioned by those who argue that they may reflect a rather narrow perspective on what musicality entails—e.g., the assumption that musical activity necessarily requires special forms of training, or that music is a pleasure product to be consumed at concerts or through recordings (for discussions see Small, 1999 ; Cross, 2003 , 2010 ; van der Schyff, 2013a , b ; Honing et al, 2015 ). With regard to this point, ethnomusicological and sociological research has revealed musical activity around the world to be central for human well-being—it is inextricable from work, play, social life, religion, ritual, politics, healing, and more (Blacking, 1973 , 1995 ; Nettl, 1983 , 2000 ; DeNora, 2000 ).…”
Section: Evolutionary Musicology and The Dichotomy Of Adaptationmentioning
confidence: 99%
See 1 more Smart Citation